The interaction between single droplet of molten tin and cooling water: Effects of tin droplet temperature and falling height. (April 2019) - Wang, Qian; Shen, Zhihe; Wang, Jiangtao; Chen, Bin; Li, ManHou; Wang, ChangJian
Highlights: Non-fragmentation, sheet expansion, sheet and granular fragmentations were observed. Droplet temperature increase promotes the droplet to break into granular solid tin. Droplet speed increase facilitates the droplet to break into small sheets. The correlation between the tin speed and the falling height was proposed. Abstract: Experimental investigation on the interaction between molten tin droplets with water was conducted employing high-speed photography. The diameter of tin droplets was around 4.0 mm to 6.3 mm. Five tin droplet temperatures (300 °C, 350 °C, 400 °C, 450 °C, 500 °C) and six falling heights (15 cm, 30 cm, 45 cm, 60 cm, 75 cm, 90 cm) were taken into account. The results show that four typical phenomena can be observed: non-fragmentation, sheet expansion, sheet fragmentation and granular fragmentation. Even for the same conditions, more than one phenomenon occurs. The tin droplet temperature and speed have a significant influence on the interaction. The increase of temperature promotes the droplet to break into granular solid tin by thermodynamic mechanism, while the increase of speed facilitates the droplet to break into small sheets of tin by a hydrodynamic mechanism. The correlation between the tin speed and the falling height was derived, and some parametric analyses were also performed.